A poet's country: landscape and nationhood in T. S. Eliot's post-conversion poetry and politics - Xu, Xiaofan (2018)
The thesis contributes to the knowledge on modernist national identity in the transnational context, with a primary focus on the agency of the rural landscape in the identity-making process. It engages with the post-conversion works of T. S. Eliot, investigates his ruralism in relation to the metropolitan and cosmopolitan aspects of modernism, and situates it within the context of late modernism where an idealised representation of rurality is exploited by various ideologies including fascism and imperialism. By drawing upon insights from transnational modernism and latest theoretical advances on cosmopolitanism, the thesis reveals through the case of Eliot that representations of rurality, local allegiances and rootedness can be emancipatory and coextensive with cosmopolitan projects. My investigation begins by examining the ruralist elements in Eliot’s poetry, pageant and translations during the decade of his conversion to the Anglican Church in 1927, and demonstrates how an emphasis on roots, inheritance and rural living is at once occasioned by and constitutes part of the cosmopolitan condition. The discussion of rootedness is then carried forward to its moral implications, namely its accused complicity with the fascist discourse of the 1930s. A reading of Eliot’s interwar play alongside texts from British surrealism reveals that the vocabulary of ‘Blood and Soil’ used as a fascist slogan can also feed into an alternative literary imagination, one that is devolutionary and anti-nationalist. The argument proceeds to Eliot’s wartime works and reveals how a transnational identity—again channelled through representations of rurality—intervenes into and resists the imperialist spatial ordering of the centre and the periphery. All these discussions of the transnational facets of Eliot’s modernist ruralism prompt a reconsideration of the widely-made association between land-writing and reactionary politics, which the thesis challenges by showing that seeds of modernity and resistance are nonetheless meted out by representations of rurality and local roots.